1982
DOI: 10.1084/jem.155.6.1785
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of natural killer cells in the murine intestinal epithelium and lamina propria.

Abstract: Morphologic and functional similarities between the lymphoid tissues of the gut and lung have shown that a common mucosal immune system is involved in the protection of mucosal sites (1). Several studies have demonstrated the relevance of antibody, particularly IgA, in mucosal immunity. However, less attention has been directed to the role of cell-mediated immunity. The recent development of methods for the isolation of mucosal Iymphoid cells (2-7) has facilitated the analysis of cytotoxic functions of lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(86 citation statements)
references
References 27 publications
3
82
0
Order By: Relevance
“…Zonulin, which can induce tight junction disassembly and increase intestinal permeability, is upregulated in T1D, and gliadin induces zonulin upregulation in the intestinal cell line Caco2 [37]. This may result in direct stimulation of NK cells present in the lamina propia by gliadin or APCs [38,39]. It has also been suggested that gluten peptides might be presented by DCs sampling the intestinal lumen [40], which may increase the crosstalking with NK cells [14], thus making it possible for gliadin to activate NK cells even in the absence of a leaky gut epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Zonulin, which can induce tight junction disassembly and increase intestinal permeability, is upregulated in T1D, and gliadin induces zonulin upregulation in the intestinal cell line Caco2 [37]. This may result in direct stimulation of NK cells present in the lamina propia by gliadin or APCs [38,39]. It has also been suggested that gluten peptides might be presented by DCs sampling the intestinal lumen [40], which may increase the crosstalking with NK cells [14], thus making it possible for gliadin to activate NK cells even in the absence of a leaky gut epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are found in the murine intestinal epithelium and in the lamina propria (5,6) and NK T cells in the gut (7). Intestinal NK cells have cytotoxic (5) and IFN-␥ production activity (6).…”
Section: Eliac Disease (Cd)mentioning
confidence: 99%
“…Intestinal NK cells have cytotoxic (5) and IFN-␥ production activity (6). The expansion of intraepithelial lymphocytes expressing CD94, a typical NK cell receptor (8), and of a subset of gut epithelium CD3 Ϫ CD56 ϩ lymphocytes (9) has been described in CD.…”
Section: Eliac Disease (Cd)mentioning
confidence: 99%
“…Lymphocytes from perfused liver were obtained according to the method described by Goossens et al (48). Intraepithelial lymphocytes (IELs) were prepared and purified through discontinuous 40%/70% Percoll gradient centrifugation as described by Tagliabue et al (49). Thymic stromal cell suspensions were prepared by digesting thymic lobes in 0.1% trypsin and 0.5 mM EDTA for 40 min at 37 o C. Digestion was stopped by addition of immunofluorescence (IF) buffer (HBSS containing 2% FBS and 0.1% NaN 3 ).…”
Section: Cell Preparation and Flow Cytometrymentioning
confidence: 99%